Metode Drill untuk Meningkatkan Prestasi Belajar Siswa Kelas XI pada Pembelajaran Al-Qur’an Hadist Materi Hidup Berkah dengan Menghormati dan Mematuhi Orang tua dan Guru - Asmayepi, Asmayepi (Sekolah Tinggi Agama Islam (STAI) Al- Kifayah Riau, 2022)
Al-Quran Hadith lessons are lessons that are very influential on everyday life. This research uses a qualitative method with a descriptive statistical approach. This research was conducted at MAN 1 Dumai City which is located on Jl. Raya Bukit Datuk Dumai in the even semester of the 2019/2020 academic year. This type of classroom action research Kurt Lewin model consists of planning, action, observation, and reflection stages which aim to improve or overcome student difficulties in learning activities, research actions are divided into two cycles (3 X 45 minutes 4 meetings). The purpose of the study was to determine whether the drill method can improve student learning achievement in Al-Quran Hadith subjects. Data collection techniques were carried out through participatory observation and classroom activities, as well as learning outcomes test instruments. To check the validity of the data, researchers used triangulation techniques, namely checking the validity of data that utilizes something else outside the data for the purpose of checking or comparing the data. The benchmark for the success of the action is seen from the percentage level of student learning completeness (KKM 85) which reaches at least 85% of the total students. The results of the study concluded that there was an increase in student learning achievement in the subject of Al-Quran Hadith material on living a blessing by respecting and obeying parents and teachers in Class XI IIS 2 at MAN 1 Kota Dumai after using the drill method has reached the minimum completeness criteria with very good results. At the end of cycle I, the value of student learning outcomes completed amounted to 25 people (81%) then increased at the end of cycle II with the number of complete students reaching 31 people (100%). The average class score of cycle I was 84.03 and cycle II was 89.19.